Morphometry of the Páez River hydrographic sub-basin, Cartago, Costa Rica - Alvarez Jiménez, María; Ramírez-Granados, Pablo; Alfaro-Jiménez, Kevin; Solís-Torres, Ligia Dina; Castro-Solís, José (Revista Geográfica de América Central., 2021)
Morphometric studies provide information on the hydrological functioning in a basin. The objective of the present study was to determine morphometric parameters in the sub-basin of the Páez River, located in the province of Cartago, Costa Rica, necessary for land use planning within the basin and its proper management. Morphometric construction was based on the 1:10,000 scale contour lines available for the Gran Area Metropolitana (translated as the Greater Metropolitan Area) and geographic information systems utilized to digitalize contour lines, drainages and watershed. Resulting from the morphometric analysis, a sub-basin area of 28.34 km2 and perimeter distance of 47.4270 km were estimated. The sub-basin is comprised of 22 micro-basins and overall exhibits a form factor value of 0.1171, thus indicating an elongated sub-basin. A compactness coefficient value of 2.4942 indicates an elongated basin. The sub-basin exhibits a concave hypsometric curve, where the peak of its altimetry distribution corresponds to altitudes between 3315 m and 980 m. The slope parameter has an average value of 29.3% slope. It is evident the role played by the Páez River sub-basin for the development of productive activities and water supply of some localities in the province of Cartago.